Changes in the foveal microstructure after intravitreal bevacizumab application in patients with retinal vascular disease - Feucht N (Dove Medical Press, 2013)
Nikolaus Feucht, Etienne Michael Schönbach, Ines Lanzl, Konstantin Kotliar, Chris Patrick Lohmann, Mathias MaierDepartment of Ophthalmology, Technical University of Munich, Munich, GermanyPurpose: To investigate changes in the area of the foveal avascular zone (FAZ) in patients with retinal vascular disease.Patients and methods: This retrospective, consecutive study examined 53 eyes of 53 patients with macular edema due to branch retinal vein occlusion in 25 patients (47.2%) and nonproliferative diabetic retinopathy in 28 patients (52.8%). The macular edema was treated with an intravitreal injection of 0.05 mL equal to 1.25 mg bevacizumab. Before and 6–8 weeks after the injection, best corrected visual acuity, slit lamp biomicroscopy of the anterior segment and fundus, optical coherence tomography, and fluorescein angiography were conducted. The FAZ was manually circumscribed on early-phase angiography images and the area of the FAZ was measured.Results: The preoperative overall mean FAZ area was 0.327 ± 0.126 mm2 (median 0.310 mm2). At the control consultation, the overall mean area was significantly larger (0.422 ± 0.259 mm2; median 0.380 mm2; P < 0.001). In the nonproliferative diabetic retinopathy subpopulation, the mean area was 0.361 ± 0.129 mm2 (median 0.330 mm2) before bevacizumab application and 0.434 mm2 at the follow-up visit (mean increase 0.071 mm2/19.7%). In the branch retinal vein occlusion group, the baseline FAZ area was 0.290 ± 0.115 mm2 and 0.407 ± 0.350 mm2 at follow-up (median 0.330 mm2; mean increase 0.117 mm2/40.3%). No cases of severe operation-associated complications were observed.Conclusion: The results confirm the safety of intravitreal bevacizumab injection in patients with macular edema due to nonproliferative diabetic retinopathy and branch retinal vein occlusion. The enlargement of the FAZ could be equivalent to an increase in retinal ischemia. These results may be transient; a potential vascular risk, however, when applying antivascular endothelial growth factor therapy in eyes with preexistent vascular disease must be considered.Keywords: foveal avascular zone, ischemia, diabetic retinopathy, branch retinal vein occlusion, anti-VEGF